Reorganization of Muscle Coordination Underlying Motor Learning in Cycling Tasks - Torricelli, Diego; De Marchis, Cristiano; d’Avella, Andrea; Tobaruela, Daniel Nemati; Barroso, Filipe Oliveira; Pons, Jose L. (Frontiers in Bioengineering and Biotechnology, 2020)
The hypothesis of modular control, which stands on the existence of muscle synergies as building blocks of muscle coordination, has been investigated in a great variety of motor tasks and species. Yet, its role during learning processes is still largely unexplored. To what extent is such modular control flexible, in terms of spatial structure and temporal activation, to externally or internally induced adaptations, is a debated issue. To address this question, we designed a biofeedback experiment to induce changes in the timing of muscle activations during leg cycling movements. The protocol consisted in delaying the peak of activation of one target muscle, using its EMG envelope as visual biofeedback. For each of the ten healthy participants, the protocol was repeated for three different target muscles, i.e. Tibialis Anterior, Gastrocnemius Medialis, and Vastus Lateralis. To explore the effects of the conditioning protocol, we analyzed changes in the activity of eight lower limb muscles by applying different models of modular motor control (i.e. fixed spatial components and fixed temporal components). Our results confirm the hypothesis that visual EMG biofeedback is able to induce changes in muscle coordination. We demonstrated that neither spatially invariant nor temporally invariant muscle synergies are able to account for the overall changes in muscle coordination after learning, whereas temporally invariant muscle synergies with adjustments in timing are able to account for most of muscle activity adaptations observed after the conditioning protocol. These results support the assumption that short-term learning processes in rhythmical tasks is built upon synergistic temporal commands that are robust to changes in the task demands.